(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article explores Attention Deficit Syndrome in children, its impact on their daily lives, and various psychological interventions and strategies to correct and manage the condition. It provides insights into the methods, results, and discusses the implications of these interventions, offering conclusions and practical suggestions for parents, educators, and healthcare professionals